Germany: Europe’s China - Paul Dobrescu; Mălina Ciocea (Romanian Journal of European Affairs)
The paper analyses Germany’s ascent not only as Europe’s most important economic power, but also as its leader. Figures show that Germany overcame the crisis; in fact the crisis legitimized its development model. Which would be Germany’s main strategic choices, confirmed by the historic evolution of the recent years? First, its option for manufacturing, which allowed Germany to turn into Europe’s factory. Second, the option for reform. “Agenda 2010”, initiated by Gerhard Schroeder in 2003, is a crucial moment in the country’s evolution. Special attention is paid to Germany’s position on the single currency. Germany’s performance is that it managed to turn the euro into a kind of European Dmark. The euro now formally “obeys” German rules, agreed upon from the very beginning, and is mainly coupled to the evolution of German economy. Germany is now sitting its most important exam: the European one. Today, Germany is Europe’s most powerful state, but it must become its leader, whose development model would be accepted throughout the continent. Some German economic options are strikingly similar to China’s.